Sex Hormones and Calcitonin Gene–Related Peptide in Women With Migraine: A Cross-sectional, Matched Cohort Study. (25th April 2023) - Raffaelli, Bianca; Storch, Elisabeth; Overeem, Lucas Hendrik; Terhart, Maria; Fitzek, Mira Pauline; Lange, Kristin Sophie; Reuter, Uwe
Abstract : Background and Objectives: Sex hormones may modulate calcitonin gene-related peptide (CGRP) release in the trigeminovascular system. We studied CGRP concentrations in plasma and tear fluid in female participants with episodic migraine (EM) and a regular menstrual cycle (RMC), female participants with EM and combined oral contraception (COC), and female participants with EM in the postmenopause. For control, we analyzed 3 corresponding groups of age-matched female participants without EM. Methods: Participants with an RMC had 2 visits: during menstruation on menstrual cycle day 2 ± 2 and in the periovulatory period on day 13 ± 2. Participants with COC were examined at day 4 ± 2 of the hormone-free interval (HFI) and between days 7 and 14 of hormone intake (HI). Postmenopausal participants were assessed once at a random time point. Plasma and tear fluid samples were collected at each visit for determination of CGRP levels with an ELISA. Results: A total of 180 female participants (n = 30 per group) completed the study. Participants with migraine and an RMC showed statistically significantly higher CGRP concentrations in plasma and tear fluid during menstruation compared with female participants without migraine (plasma: 5.95 pg/mL [IQR 4.37–10.44] vs 4.61 pg/mL [IQR 2.83–6.92], p = 0.020 [Mann-Whitney U test]; tear fluid: 1.20 ng/mL [IQR 0.36–2.52] vs 0.4 ng/mL [IQR 0.14–1.22], p = 0.005 [Mann-Whitney U test]). In contrast, female participants with COC and in the postmenopause had similar CGRP levels in the migraine and the control groups. In migraine participants with an RMC, tear fluid but not plasma CGRP concentrations during menstruation were statistically significantly higher compared with migraine participants under COC ( p = 0.015 vs HFI and p = 0.029 vs HI, Mann-Whitney U test). Discussion: Different sex hormone profiles may influence CGRP concentrations in people, with current or past capacity to menstruate, with migraine. Measurement of CGRP in tear fluid was feasible and warrants further investigation.